SNIa DETECTION ANALYSIS RESULTS FROM REAL AND SIMULATED IMAGES USING SPECIALIZED SOFTWARE - Reyes, Juan Pablo; Hernández Hoyos, Marcela; Fouchez, Dominique (Revista mexicana de astronomía y astrofísica, 2024)
The detection of transient events, Type Ia supernovae in particular, has become an important research subject in today's astronomy. We use as a base tool the software suite for astronomical image processing called LSSTsp and adapt it to assemble a type Ia supernova detection pipe. We study some straightforward changes on the overall pipeline by selecting better quality inputs to perform a coaddition of reference images, we analyze the different residual sources detected on the difference images and, lastly, we build light curves by taking into account the features of detected difference image analysis sources. Finally, we build a catalog of supernova candidates by using a random forest classification, and check the relevance these additions. We reduced the overall source detection density with our changes while finding between 82% and 85% of the present Type Ia supernovae.